Displaced : life in the Katrina diaspora - Weber, Lynn; Peek, Lori A. (Katrina bookshelf., 2012)
Hurricane Katrina forced the largest and most abrupt displacement in U.S. history. About 1.5 million people evacuated from the Gulf Coast preceding Katrinas landfall. New Orleans, a city of 500,000, was nearly emptied of life after the hurricane and flooding. Katrina survivors eventually scattered across all fifty states, and tens of thousands still remain displaced. Some are desperate to return to the Gulf Coast but cannot find the means. Others have chosen to make their homes elsewhere. Still others found a way to return home but were unable to stay due to the limited availability of social services, educational opportunities, health care options, and affordable housing.